Analisis implementasi standar pelayanan minimal (SPM) bidang pelayanan kesehatan hipertensi di Puskesmas X Kabupaten Malang - Renawati, Anggi; Paramita, Farah; Adi, Sapto; Supriyadi, Supriyadi (Talenta Publisher, 2025)
Minimum Service Standards (MSS) for health emphasize the importance of the type and quality of basic services to achieve optimal and equitable health services, especially in the health sector of non-communicable diseases, which continue to increase in prevalence. Non-communicable diseases (NCDs), especially hypertension, are health problems which cases continue to increase. The prevalence of hypertension in 2018 was 34.11%, decreasing to 30.8% in 2023, but this figure has not met the national target. East Java ranks fourth with the highest prevalence of hypertension at 34.30%. The third lowest hypertension service achievement is Malang Regency. Puskesmas X had a low hypertension treatment rate of 12.71% in 2023. The purpose of this study was to analyze the implementation of MSS in hypertension health services at Puskesmas X and identify inhibiting factors based on input, process, and output variables. This study used a qualitative method with in-depth interviews involving 11 informants with an interview guide instrument and researchers conducted observations with an observation sheet instrument to record field data. This study used source triangulation and method triangulation. The results showed that hypertension MSS implementation at Puskesmas X faced several challenges, particularly limited human resources, suboptimal training, lack of educational media, weak cross-sector coordination, and ineffective data recording and reporting. Although MSS achievement increased from 3.7% (2021) to 31.3% (2024), it is still far from the national target of 100%. Overall, improvements in MSS implementation in hypertension health services at Puskesmas X have not fully met the set targets.